2014
DOI: 10.1186/1472-6874-14-19
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the utilisation of postnatal care services among the mothers of Nepal: analysis of Nepal Demographic and Health Survey 2011

Abstract: BackgroundPostnatal care is essential to save the life of the mother and newborn. Knowledge on the determinants of postnatal care assists the policy makers to design, justify and implement appropriate interventions. The current study aimed to analyse the factors associated with utilisation of postnatal care services by mothers in Nepal based on the data from Nepal Demographic and Health Survey (NDHS) 2011.MethodsThis study utilised the data from NDHS 2011. The association between utilisation of at least one po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

73
145
10
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(235 citation statements)
references
References 27 publications
(51 reference statements)
73
145
10
7
Order By: Relevance
“…Low rates of EBFI have been also recorded in South East Asia and Western Nepal where one in four babies receive breast milk within the first hour of birth. 9 Similar findings od delayed breastfeeding initiation were recorded in North Central Province of Sri-Lanka, Pakistan, India with initiation rates ranging from 29 to 45%. 10 Findings of the study revealed a significant Pearson Correlation between EBFI and neonatal sepsis at 0.01 levels (2 tailed) at day 3 and day 7.…”
Section: Discussionsupporting
confidence: 67%
“…Low rates of EBFI have been also recorded in South East Asia and Western Nepal where one in four babies receive breast milk within the first hour of birth. 9 Similar findings od delayed breastfeeding initiation were recorded in North Central Province of Sri-Lanka, Pakistan, India with initiation rates ranging from 29 to 45%. 10 Findings of the study revealed a significant Pearson Correlation between EBFI and neonatal sepsis at 0.01 levels (2 tailed) at day 3 and day 7.…”
Section: Discussionsupporting
confidence: 67%
“…The postpartum period starts about an hour after the delivery of the placenta and includes the following six weeks. [4] It is widely accepted that the use of maternal health services helps in reducing maternal morbidity and mortality. However, the utilization of maternal health services is a complex phenomenon influenced by many factors.…”
Section: Introductionmentioning
confidence: 99%
“…Lohusa bakımı alma durumu ve lohusa bakımı alınmasını etkileyen çeşitli kültürel, ekonomik ve biyolojik faktörler ulusal ve uluslararası çalışmalarda belirlenmeye çalışılmıştır. 6,7,11 Ancak, gelinen süreçte kadınların tamamının lohusa bakımı alması, lohusa bakımını içerik açısından değerlendirmeye yöneltmiş; içeriğin kalitesini etkileyen faktörlere yönelik analitik değerlendirme yapmayı zorunlu kılar hale gelmiştir. Araştırmada, sosyodemografik, biyodemografik ve sağlık hizmet kullanımı ile ilgili bağımsız değişkenlerin lohusa bakım içerik puan kategorisi üzerine etkisi olmadığı, diğer bir deyişle çeşitli kültürel, ekonomik ve biyolojik faktörlerin lohusa bakım içeriğini etkilemediği belirlenmiştir.…”
Section: -İçeriği Etkileyen Faktörlerunclassified
“…6 Doğum sonrası bakım hizmetleri verilirken, emzirme, kişisel hijyen, aile planlaması gibi konularda eğitim verilerek, anne ve bebeğe postnatal demir, A ve D vitamini vs desteği sağlanarak anne ve bebeğin daha optimal sağlık hizmeti da sağlanabilir. 7 Yapılan ulusal çalışmalarda, ölen annelerin %25,0'inin ve neonatal ölümlerin yarısının doğum sırasında ve doğum sonrası ilk 24 saat içinde gerçekleştiği ve bu oranların doğumdan sonraki ilk haftanın sonunda sırasıyla %60,0 ile üçte ikiye çıktığı bildirilmektedir. 8 Dünya'nın birçok ülkesinde olduğu gibi, Türkiye'de de anne ölümleri için risk oluşturabilecek faktörler belirlenerek bu faktörlerin eliminasyonuna yönelik ulusal rehberler hazırlanmış ve uygulamaya koyulmuştur (Doğum Sonrası Bakım Yönetim Rehberi: DSB-YR).…”
Section: Introductionunclassified